Tandospirone, a 5-HT1A partial agonist, ameliorates aberrant lactate production in the prefrontal cortex of rats exposed to blockade of N-methy-D-aspartate receptors; Toward the therapeutics of cognitive impairment of schizophrenia - Uehara, Takashi; Matsuoka, Tadasu; Sumiyoshi, Tomiki (Frontiers in Behavioral Neuroscience, 2014)
Rationale Augmentation therapy with serotonin-1A (5-HT1A) receptor partial agonists has been suggested to improve cognitive deficits in patients with schizophrenia. Decreased activity of prefrontal cortex may provide a basis for cognitive deficits of the disease. Lactate plays a significant role in the supply of energy to the brain, and glutamatergic neurotransmission contributes to lactate production. Objectives and methods The purposes of this study were to examine the effect of repeated administration (once a daily for 4 days) of tandospirone (0.05 and 5 mg/kg) on brain energy metabolism, as represented by extracellular lactate concentration (eLAC) in the medial prefrontal cortex (mPFC) of young adult rats.. Results Four-day treatment with MK-801, an NMDA-R antagonist, prolonged eLAC elevation induced by foot shock stress (FS). Co-administration with the high-dose tandospirone suppressed prolonged FS-induced eLAC elevation in rats receiving MK-801, whereas tandospirone by itself did not affected eLAC increment. Conclusions These results suggest that stimulation of 5-HT1A receptors ameliorates abnormalities of energy metabolism in the mPFC due to blockade of NMDA receptors. These findings provide a possible mechanism based on brain energy metabolism by which 5-HT1A agonism improve cognitive impairment in schizophrenia and related disorders.